2020
DOI: 10.1136/bmjopen-2020-037592
|View full text |Cite
|
Sign up to set email alerts
|

Examining the prevalence, correlates and inequalities of undiagnosed hypertension in Nepal: a population-based cross-sectional study

Abstract: ObjectiveTo examine the prevalence, correlates and sociodemographic inequalities of undiagnosed hypertension in Nepal.DesignThis study used cross-sectional 2016 Nepal Demographic and Health Survey (NDHS) data. Undiagnosed patients with hypertension were defined as an NDHS respondent who was diagnosed as hypertensive (systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg) during the survey, but never took any prescribed anti-hypertensive medicine to lower/control blood pressure and was neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
4
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 42 publications
6
60
4
6
Order By: Relevance
“…This expression is a good description of the scenario of patients with hypertension in many regions of the world and in countries such as Peru. In low-and middle-income countries, it has been reported that the prevalence of undiagnosed hypertension is between 12% and 50% [ 6 , 8 , 26 , 27 ]. The value found in Peru is above this range, with more than half of adults with hypertension presenting undiagnosed hypertension, making this an important public health problem.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This expression is a good description of the scenario of patients with hypertension in many regions of the world and in countries such as Peru. In low-and middle-income countries, it has been reported that the prevalence of undiagnosed hypertension is between 12% and 50% [ 6 , 8 , 26 , 27 ]. The value found in Peru is above this range, with more than half of adults with hypertension presenting undiagnosed hypertension, making this an important public health problem.…”
Section: Discussionmentioning
confidence: 99%
“…The following independent variables were considered: age in years (18–29/30-49/50–69/70 or more), gender (female/male), ethnicity (non native, native, afro-peruvian), educational level (none or pre-school/primary education/secondary education/higher education), marital status (single/married/widowed, divorced, or separated), health insurance (yes/no), body mass index (underweight or normal/overweight/obesity), physical or psychological limitation (yes/no), depressive symptoms (determined by a score of ten or more in the Patient Health Questionnaire-9 [PHQ-9] screening test in the 14 days prior to the survey [yes/no]), diabetes (yes/no), smoking status (if smoked cigarettes in the last 30 days [yes/no]), binge drinking (consumption of five and four or more alcoholic beverages on the same occasion for men and women, respectively, in the last 30 days prior to the survey [yes/no]), wealth quintile (richest/rich/middle/poor/poorest), area of residence (urban/rural), natural region of residence (Jungle/Andean/Coast), and altitude in meters above sea level (MASL) The selection and inclusion of these independent variables in the study were based on a literature review [ 7 , 8 , 9 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations